Análise e otimização exergoeconômica de um sistema de destilação industrial para produção de bioetanol - Rocha, Lucas Bonfim (2015)
Among all industrial separation processes, distillation is one of the largest energy consumers. Hence the search for energy optimization methods for distillation columns is justified. The optimization of parameters such as feed stage, reflux ratio, number of stages, can be obtained from analysing the exergy losses profile of the column, which in turn depends on the determination of the thermodynamic properties of the set of streams inside the column. This study aims to realize the exergoeconomic optimization of an industrial system of distillation columns capable of producing hydrated ethanol, using the Aspen Plus software for simulation of the system under study with Radfrac as a rigorous method for solving the MESH equations of the columns applying the appropriate thermodynamic models. The design and operational parameters of the column, already optimized from an energy point of view, are then evaluated and able to allow an economic optimization to new operating conditions. The results show that it was possible to achieve the thermodinamyc optimization of the distillation columns without violating the critical specifications of the process. The optimized process loses less energy than the original process, but requires greater investment. This result directed us to investigate if the process is valid economically. The thermoeconomic evaluation of the process led us to conclude that in this work, even with increased investment to implement a process of greater efficiency, it resets viable in time and provides a continuous cost savings by requiring less energy